Odpowiedzi

  • Użytkownik Zadane
2010-03-31T17:03:08+02:00
A)f(x)=(x-2)(x²-9)=0
3^3-9x-2x^2+18=0
X^3-2x^2-9x+18=0
X^2(x-2)-9(x-2)=0
(x^2-9)(x-2)=0
(x^2-9)=0 v (x-2)=0
x^2=9 v x=2
x=3 v x=-3 v x=2


b)f(x)=(x²+4x+4)(x²-3)=0
(x²+4x+4)=0 v (x²-3)=0
a=1 b=4 c=4 v x^2=3
delta=b^2 - 4ac v x=pierwiastek z 3 v x=- pierwiastek z 3
delta=16-16
delta=0
x0=-b/2a=-4/2=-2


c)f(x)=(6x²-5x+1)(1-4x²)=0
(6x²-5x+1)=0 v (1-4x²)=0
a=6 b=-5 c=1 v -4x^2=-1
delta=b^2-4ac v x=1/2 v x=-1/2
delta=25-24=1
x1=-b-pierwiastek z delty/2a=5-1/12=1/3
x2=-b+pierwiastek z delty/2a=5+1/12=1/2


d)f(x)-x³+5x²+x-5=0
-x^2(x-5)+1(x-5)=0
(-x^2+1)=0 v (x-5)=0
-x^2=-1
(nie zachodzi) v x=5


e)f(x)=-12x³+8x²+3x-2=0
-4x^2(3x-2)+1(3x-2)=0
(-4x^2 +1)=0 v (3x-2)=0
-4x^2=-1 v 3x=2
x^2=1/4 v x=2/3
x=1/2 v x=-1/2
4 5 4